Faktor-Faktor Yang Berhubungan Dengan Perilaku Calon Pengantin Terhadap Pelaksanaan Skrining Pranikah : Implementation of Premarital Screening - Ika Tawanti (Indonesian Journal of Midwifery Scientific, 2023)
Based on the results of the 2017 IDHS obtained from interviews with 70% of women who answered that the examination needed before marriage is a physical examination. During 2020 the number of women of childbearing age who came to health care facilities to receive premarital screening services decreased compared to 2019, not reaching 5 percent of the total number of WUS in Banten Province. Based on the results of the Tangsel KESGA 2022 report, the Pondok Ranji Health Center has just implemented an MOU for pre-marital screening services with the KUA in March 2022. During September 2022 to December 2022 at the Pondok Ranji Health Center, there were 15 prospective brides who had pre-marital screening. The purpose of this study was to determine the factors related to the behavior of the bride and groom in carrying out pre-marital screening in the Pondok Ranji Health Center area, South Tangerang in 2023. This study used an analytic descriptive method with a cross-sectional design, a sampling technique with accidental sampling with a total of 40 respondents. This research was conducted in January 2023-February 2023. The statistical test results explained that there was a significant relationship between age (p-value= 0.020) OR=9.714, education (p-value=0.025) OR=6.364, occupation (p-value= 0.032) OR= 7.250, knowledge (p-value= 0.034) OR=7.467, attitude (p-value= 0.020) OR=0.103, family support (p-value= 0.044) OR=5.750 with the behavior of the prospective bride and groom towards premarital screening. With this research, it is hoped that the bride and groom will be able to take pre-marital screening examinations in accordance with the standards recommended by the government, and for health workers it is hoped that they will make efforts to increase the coverage of pre-marital screening for couples at the Pondok Ranji Health Center through direct counseling to the public, especially the prospective bride and groom.